2018
DOI: 10.1097/ccm.0000000000003356
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assessment of the Change in Carotid Corrected Flow Time in Fluid Responsiveness in Undifferentiated Shock

Abstract: Change in carotid corrected flow time can predict fluid responsiveness status after a passive leg raise maneuver. Using point-of-care ultrasound to assess change in carotid corrected flow time is an acceptable and reproducible method for noninvasive identification of fluid responsiveness in critically ill patients with undifferentiated shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 50 publications
4
90
0
2
Order By: Relevance
“…Four hundred sixty‐five articles were found through the systematic search. Of these, 17 were determined to meet inclusion for the study (Figure ) . A total of 956 patients were included in the identified studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four hundred sixty‐five articles were found through the systematic search. Of these, 17 were determined to meet inclusion for the study (Figure ) . A total of 956 patients were included in the identified studies.…”
Section: Resultsmentioning
confidence: 99%
“…These studies evaluated at least 1, but occasionally more, carotid artery ultrasound measurement in relation to volume status. The most commonly used carotid measure was corrected flow time (FTc; 9 of 17 [53%]) . These studies recorded either absolute values or the absolute change and relative percentage change of FTc after PLR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that measuring changes in pulse pressure variation or stroke volume variation that occur when increasing tidal volume from 6 mL/kg predicted body weight to 8 mL/kg may add value in predicting fluid responsiveness [62]. Ultrasound measurements that predict fluid responsiveness include global end-diastolic volume index [63], velocity time integral of the Doppler signal across the left ventricular outflow tract [64,65], and carotid artery flow [66]. Respiratory variation in inferior vena cava diameter is a commonly used measurement, but a recent meta-analysis suggested limited ability to predict fluid responsiveness, particularly in spontaneously breathing patients [67].…”
Section: How Much Fluid To Givementioning
confidence: 99%
“…Previous studies on CCABF were conducted on healthy volunteers [57,58], ICU patients [18,[59][60][61], and peri-operative patients [62,63]. To our knowledge no studies have investigated the accuracy of SSAD in identifying fluid responders in spontaneously breathing patients in any clinical setting.…”
Section: Discussionmentioning
confidence: 99%